Anti-inflammatory effects of Banisteriopsis caapi and beta-carbolines in neuronal cells: potential implications for neuro-COVID - Bianco, Laura Seixas; Nicoliche, Tiago; Corrêa-Neto, Nelson Francisco; Lanaro, Rafael; Caetano, Ariadiny L.; Prado, Carla Maximo; Ureshino, Rodrigo Portes; Tibério, Iolanda de Fátima Lopes Calvo; Righetti, Renato Fraga; Stilhano, Roberta Sessa; Linardi, Alessandra (Frontiers in Pharmacology, 2026)
BackgroundNeuroinflammation plays a central role in neurodegenerative diseases such as Alzheimer’s and Parkinson’s, along with depression, anxiety, and infectious diseases including COVID-19. Harmine and harmaline, β-carboline alkaloids from Banisteriopsis caapi, exhibit immunomodulatory, anti-inflammatory, and neuroprotective properties. In this study, we aimed not only to investigate the anti-inflammatory and neuroprotective effects of β-carbolines and B. caapi extract on a lipopolysaccharide (LPS)-induced neuroinflammation model using SH-SY5Y cells and their impact on severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) receptor expression but also to compare cytokine levels in plasma from intensive care unit (ICU) and non-ICU COVID-19 patients, thereby providing clinical context for the inflammatory response.MethodsSH-SY5Y cells were treated with LPS and incubated with harmine, harmaline, or B. caapi extract. Cell viability was assessed using the MTT assay. Cytokine expression was quantified by ELISA, and receptor gene expression was analyzed using RT-qPCR. Plasma was obtained from the Hospital das Clínicas of the University of São Paulo Medical School (HCFMUSP) biobank.ResultsIL-6 was high in ICU patients; LPS increased IL-6 and TNF-α cytokine levels in cells, whereas harmine and harmaline significantly reduced both cytokines. B. caapi extract decreased LPS-induced NF-κB and TNF-α but did not affect IL-6. Harmine also reduced NF-κB expression. None of the treatments altered TMPRSS11D or furin, and harmaline showed no effect on ACE2. In contrast, the extract upregulated ACE2, whereas harmine induced a modest increase. Only harmine and harmaline reduced TMPRSS2 expression.Conclusionβ-carbolines and B. caapi extract attenuate LPS-induced cytokine production in SH-SY5Y cells, supporting their anti-inflammatory and neuroprotective potential. The extract and β-carbolines also modulate ACE2 and TMPRSS2 expressions, suggesting relevance to mechanisms associated with neuro-COVID.